2005
DOI: 10.1002/ejic.200500349
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Neutral Coligand on the Spectroscopic Properties and Crystal Structures of Lithium Tri(tert‐butyl)silylarsanides of the Type[(L)LiAs(H)SitBu3] (L = DME, THF)

Abstract: The reaction of [(dme)LiAsH 2 ] with F 3 CSO 3 SitBu 3 yields tri-(tert-butyl)silylarsane (1). The reaction of 1 with n-butyllithium in 1,2-dimethoxyethane gives [(dme)LiAs(H)SitBu 3 ] 2 (2), whereas the lithiation of 1 in THF leads to the formation of the one-dimensional polymer [(THF)LiAs(H)SitBu 3 ] ϱ (3). The Li-As bond lengths of both of these compounds show a similar value of approximately 260 pm. However, the smaller co-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…For example, Westerhausen showed that the calcium bis-amide Ca­[N­(SiMe 3 ) 2 ] 2 was able to deprotonate the silylated primary arsine H 2 As–Si i Pr 3 ( 1215 ) generating a new calcium bis­(silyl)­arsenide [Ca­(THF) 4 {AsH­(Si i Pr 3 )} 2 ] ( 1216 , eq 103 ). Related silylarsenides [As­(H)­SiR 3 ] − of strontium, barium, magnesium, zinc and lithium were also reported. …”
Section: Molecular Hydrides Of Group 15 Metals (Arsenic Antimony and ...mentioning
confidence: 99%
“…For example, Westerhausen showed that the calcium bis-amide Ca­[N­(SiMe 3 ) 2 ] 2 was able to deprotonate the silylated primary arsine H 2 As–Si i Pr 3 ( 1215 ) generating a new calcium bis­(silyl)­arsenide [Ca­(THF) 4 {AsH­(Si i Pr 3 )} 2 ] ( 1216 , eq 103 ). Related silylarsenides [As­(H)­SiR 3 ] − of strontium, barium, magnesium, zinc and lithium were also reported. …”
Section: Molecular Hydrides Of Group 15 Metals (Arsenic Antimony and ...mentioning
confidence: 99%